Interactive Effects of Epichloë Endophytes and Arbuscular Mycorrhizal Fungi on Saline-Alkali Stress Tolerance in Tall Fescue - Liu, Hui; Tang, Huimin; Ni, Xiaozhen; Zhang, Yajie; Wang, Yingchao (Frontiers in Microbiology, 2022)
Epichloë endophytes and arbuscular mycorrhizal fungi (AMF) are two important symbiotic microorganisms of tall fescue (Lolium arundinaceum). Our research explores the combined effects of endophytes and AMF on saline-alkali stress. The finding revealed that a significant interaction between Epichloë endophytes, AMF, and saline-alkali stress occurred in the growth and physiological parameters of tall fescue. Endophyte infection significantly enhanced tall fescue resistance to saline-alkali stress by increasing shoot and root biomass, nutrient uptake (organic carbon, total nitrogen, and total phosphorus concentration), and accumulation of K+ while decreasing Na+ concentration. Furthermore, the beneficial effect of endophytes was enhanced by the beneficial AMF, Claroideoglomus etunicatum (CE), but was reduced by the detrimental AMF, Funneliformis mosseae (FM). Our findings highlight the importance of interactions between multiple microorganisms for plant performance under saline-alkali stress.